THE USE OF BRAINSTORMING STRATEGY TO IMPROVE THE WRITING SKILL OF THE NINTH-GRADE STUDENTS - Ni Komang Dea Astuti; Ni Made Wersi Murtini; Ida Ayu Made Sri Widiastuti (Academic Journal on English Studies (AJOES), 2023)
This classroom action research's goal was to determine whether brainstorming and flashcards could enhance the ninth-grade students’ writing abilities at SMP Negeri Hindu 2 Sukawati. A group problem-solving method called brainstorming involves the impromptu sharing of original ideas and solutions. A tool that is utilized to support the application of the brainstorming technique is the flashcard. In particular, the IX B class at SMP Negeri Hindu 2 Sukawati in the academic year 2022/2023 was the focus of the discussion. There were 40 subjects in total, with 16 female and 24 male participants. Planning, action, observation, and reflection were the four processes for each of the two cycles that this research was conducted in. The pre-test, post-test 1, post-test 2, and questionnaire data were analyzed quantitatively and quantitatively. The outcome demonstrated that brainstorming and flashcards together can help the ninth-grade students at SMP Negeri Hindu 2 Sukawati in the academic year 2022/2023 to improve their writing skills.